Membaca Chairil Anwar Melalui Psikokritik - Mulyo Hadi Purnomo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The poem "Aku" by Chairil Anwar is often identified with the spirit of nationalism. Because indeed Chairil Anwar is widely known as the pioneer of the 45th Generation which is synonymous with independence and nationalism. Psychocritical readings by looking at superpositions / piles of text indicate the passion of tanatos (death) which is even more prominent.